APPLYING CORRECTION GAME IN TEACHING NOMINALIZATION TO IMPROVE STUDENTSâ WRITING OF DISCUSSION TEXT - Fasha, Siti Aisyah Dailla; Bachtiar, Hasna Parida (Research And Innovation In Language Learning (RILL), 2018)
Related to curriculum 2013 which is currently applied in Indonesia, students are required to learn genres and later write the text independently. One of the genre types learned at higher level of students, grade XII is argumentative discussion. However, they often face difficulties in delivering and elaborating their opinions and reasons in writing discussion text since they do not know exactly how to do so. Using qualitative design and Systemic Functional Linguistics analysis, this study attempts to find out the analysis result of the discussion text written by expert in which becomes the basic reference to identify the main problem found in the studentsâ texts which later help to discover pedagogical implication to improve their writings. The results show that the expertâs text is considered as an ideal model of discussion text. Besides, there are two problems appeared in the studentsâ texts in term of the situational contexts such as lack of nominalization and the absence of passive sentence. The former becomes the major problem since it is assumed to affect the appearance of the latter. The implementation of Correction Game which is integrated in the genre based approach teaching reveals as pedagogical implication.